North-South Technology Diffusion, Regional Integration, and the Dynamics of the Natural Trading Partners Hypothesis - Schiff, Maurice; Wang, Yanling (World Bank, Washington, D.C., 2013)
Based on static analysis, a number of studies argue that forming a regional trade agreement is more likely to raise welfare if member countries are "natural trading partners," while other studies claim that the opposite is true. Schiff and Wang look at the argument from a dynamic viewpoint by examining the impact of North-South trade on technology diffusion and total factor productivity (TFP) in the South. Specifically, it examines the impact on TFP in the Republic of Korea, Mexico, and Poland of trade with Japan, Canada plus the United States (North America) and the European Union. Using industry-level data, they find that (1) technology diffusion and productivity gains tend to be regional: Korea benefits mainly from trade with Japan, Mexico with the United States, and Poland with the European Union; and (2) though these results suggest that the dynamic version of the "natural trading partners" hypothesis holds for all three countries, careful analysis shows that it holds for Korea and Mexico but not necessarily for Poland.